2019
DOI: 10.1002/ecy.2850
|View full text |Cite
|
Sign up to set email alerts
|

Negative plant–soil feedbacks are stronger in agricultural habitats than in forest fragments in the tropical Andes

Abstract: There is now strong evidence suggesting that interactions between plants and their species-specific antagonistic microbes can maintain native plant community diversity. In contrast, the decay in diversity in plant communities invaded by nonnative plant species might be caused by weakening negative feedback strengths, perhaps because of the increased relative importance of plant mutualists such as arbuscular mycorrhizal fungi (AMF). Although the vast majority of studies examining plant-soil feedbacks have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 83 publications
(238 reference statements)
0
17
0
Order By: Relevance
“…Nonetheless, exotic plants have not experienced uniformly positive PSF, for example, Andonian et al (2011) indicated that an invasive weed experienced negative PSF; Crawford and Knight (2017) found that Lespedeza cuneata experienced positive PSF in invaded soils only in the absence of competition; and for some plant species, a positive PSF was observed in a glasshouse but not in the field ((Schittko et al, 2016). These discrepancies suggest that the PSF experienced by the exotic invaders is context dependent and may involve the soil habitat type in which the plants grow (Pizano et al, 2019).…”
mentioning
confidence: 99%
“…Nonetheless, exotic plants have not experienced uniformly positive PSF, for example, Andonian et al (2011) indicated that an invasive weed experienced negative PSF; Crawford and Knight (2017) found that Lespedeza cuneata experienced positive PSF in invaded soils only in the absence of competition; and for some plant species, a positive PSF was observed in a glasshouse but not in the field ((Schittko et al, 2016). These discrepancies suggest that the PSF experienced by the exotic invaders is context dependent and may involve the soil habitat type in which the plants grow (Pizano et al, 2019).…”
mentioning
confidence: 99%
“…Positive feedbacks are expected to reduce species diversity 12 . In nature, net microbial PSF comprises the combined effects of pathogens (−) and mutualists (+) [13][14][15] .…”
mentioning
confidence: 99%
“…There is a pervasive lack of data about how biotic factors influence carbon storage. Biotic interactions play a prominent role in carbon dynamics; for example, feedbacks between plants and their associated soil organisms can influence species growth (Pizano et al, 2019), changes in aboveground arthropods can determine herbivory (Ebeling et al, 2014), and soil macrofauna can drive leaf-litter decomposition (Cárdenas et al, 2017;Four et al, 2019), thus making major contributions to carbon and nutrient cycling in tropical ecosystems (McNaughton et al, 1989;Metcalfe et al, 2014). The effects of biomass and faunal, fungal, and bacterial diversity on different functions such as decomposition, litterfall, aboveground biomass, and fine root production are little known in upland forests.…”
Section: General Bibliographic Trendsmentioning
confidence: 99%